Endomicroscopy in bile duct: Inflammation interferes with pCLE applied in the bile duct: A prospective study of 54 patients. Issue 2 (1st April 2013) - Caillol, Fabrice; Bories, Erwan; Poizat, Flora; Pesenti, Christian; Esterni, Benjamin; Monges, Geneviève; Giovannini, Marc
Abstract : Background: The preoperative diagnosis of biliary stenosis is associated with low accuracy. As a consequence, probe‐based confocal laser endomicroscopy (pCLE), an in‐vivo histological imaging technique, was applied in the bile duct. The aim of this study was to establish whether previous inflammation of the bile duct affects confocal interpretation. The findings from pCLE were compared in two groups of patients: those in whom there had been no cholangitis nor stenting and those in whom stents had been used and subsequently retrieved or who had suffered cholangitis. Patients and methods: pCLE was performed on 54 patients (mean age 66 years; 31 men, 23 women) from September 2008 to July 2011. Patients were divided in two groups: group 1: 39 patients who had not undergone a biliary procedure in the month preceding the pCLE procedure; and group 2: 15 patients who had undergone stent placement or presented with cholangitis in the month preceding the pCLE procedure. Endoscopic and pCLE data were collected prospectively. pCLE results were compared to benchmark histology (surgery, endoultrasonography, percutaneous biopsy). Patients with a benign stricture who did not undergo operation were followed for 1 year. pCLE images of the bile duct were obtained during endoscopic retrograde cholangiopancreatography procedures. pCLE images were interpreted prospectively using the Miami classification in vivo and in real time. Results: In group 1, sensitivity, specificity, and accuracy were 88, 83, and 87%, respectively. In group 2, sensitivity, specificity, and accuracy were 75, 71, and 73%, respectively. Diagnostic accuracy of pCLE was lower when applied to group 2 ( p < 0, 001). The investigation is less reliable in bile ducts affected by inflammation from cholangitis or previous stenting. Conclusions: Inflammatory lesions of the bile duct interfere with interpretation of pCLE. A refined pCLE description of inflammatory lesions should improve accuracy of pCLE in bile duct stenosis.